2023
DOI: 10.1111/imr.13214
|View full text |Cite
|
Sign up to set email alerts
|

The role of efferocytosis‐fueled macrophage metabolism in the resolution of inflammation

Abstract: SummaryThe phagocytosis of dying cells by macrophages, termed efferocytosis, is a tightly regulated process that involves the sensing, binding, engulfment, and digestion of apoptotic cells. Efferocytosis not only prevents tissue necrosis and inflammation caused by secondary necrosis of dying cells, but it also promotes pro‐resolving signaling in macrophages, which is essential for tissue resolution and repair following injury or inflammation. An important factor that contributes to this pro‐resolving reprogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 196 publications
0
7
0
Order By: Relevance
“…5 Efferocytosis profoundly impacts macrophage metabolism, as cellular products taken up must be degraded or incorporated into active biosynthetic pathways. 6 Recent data indicate that functional and metabolic aspects of macrophage efferocytosis are coordinated through class III histone deacetylases (HDACs), or SIRTs. SIRTs are the only family of NAD + -dependent HDACs, and have been strongly implicated in metabolism, stress responses, apoptosis, and aging.…”
Section: Article See P 631mentioning
confidence: 99%
“…5 Efferocytosis profoundly impacts macrophage metabolism, as cellular products taken up must be degraded or incorporated into active biosynthetic pathways. 6 Recent data indicate that functional and metabolic aspects of macrophage efferocytosis are coordinated through class III histone deacetylases (HDACs), or SIRTs. SIRTs are the only family of NAD + -dependent HDACs, and have been strongly implicated in metabolism, stress responses, apoptosis, and aging.…”
Section: Article See P 631mentioning
confidence: 99%
“…Importantly, we observed that the predominate biological process and canonical IPA pathway identified for C4 was oxidative phosphorylation. Oxidative phosphorylation in monocytes is important for resolving inflammation by providing ATP for cellular functions, supporting phagocytosis and efferocytosis, maintaining redox balance, facilitating metabolic reprogramming, and enabling the production of specialized pro-resolving lipid mediators [ 55 , 56 ]. At the peak of inflammation, immune cells preferentially use glycolysis as a source of energy.…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79][80][81] The ability for macrophages to metabolize the "cargo" of apoptotic cells is also critically important to efficient dead cell clearance, which is elegantly reviewed here. 82 For example, the breakdown of apoptotic cells provides metabolic fuel for programs such as fatty acid oxidation (FAO) and oxidative phosphorylation (OXPHOS), as well as aerobic glycolysis. [77][78][79][80][81] Yurdagul et al have demonstrated the necessary role of amino acid metabolism and continual efferocytosis.…”
Section: Macrophages Can Engulf Multiple Apoptotic Cells and Mechanismsmentioning
confidence: 99%